Pengaruh Budaya Lokal terhadap Kepuasan Tamu di Hotel Royal Ambarrukmo Yogyakarta - Rajid Ibnu Shina Prasetya; Kris Cahyani Ermawati; Suparwi Suparwi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research was conducted at the Royal Ambarrukmo Hotel Yogyakarta using a qualitative descriptive approach supported by data collection methods in the form of interviews, observations, documentation, and guest reviews. Data analysis was carried out using the Miles & Huberman model as well as data triangulation to ensure the validity of the findings. Based on variables X (influence of local culture) and variable Y (guest satisfaction), this study aims to find out the extent to which the application of local culture can affect the level of guest satisfaction. The results of the study show that local culture is applied through various aspects, including the use of traditional ornaments in hotel interior design, services that prioritize Javanese cultural ethics, and the presentation of regional culinary specialties. This effort is not only a marketing strategy, but also creates a different and memorable experience for guests. According to the management, local culture is an identity as well as an added value that can significantly increase guest satisfaction. Guests feel like they're getting a unique experience that is not only functional, but also emotional. This emotional attachment affects guest loyalty to return, thus having a positive impact on the sustainability of the hotel business. In conclusion, local culture plays an important role as a differentiating factor that improves the quality of service and strengthens the image of Hotel Royal Ambarrukmo Yogyakarta in the midst of fierce competition in the hospitality industry. Thus, the application of local culture can be used as a sustainable strategy to create a competitive advantage.